GROUNDWATER POTENTIAL INVESTIGATION USING 1-D ELECTRICAL RESISTIVITY TECHNIQUE AT NIGER STATE POLYTECHNIC ZUNGERU, ZUNGERU MAIN CAMPUS, NIGER STATE, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2022)
Electrical resistivity method employing vertical electrical sounding was carried out with aim to investigate groundwater potential at Niger State Polytechnic, Zungeru, Niger State. Ten points were selected at different locations within the campus for vertical electrical sounding (VES), using Schlumberger protocol. Maximum current electrodes separation (AB) of 120m was used. The investigation was carried out using Terrameter PE 02 SAS 300 system. The survey was able to investigate groundwater potential of the area. The IPI2win software was used for data analysis. The geologic section derived from geoelectric parameters revealed three subsurface layers. The first layer is interpreted as topsoil, the second layer is inferred to be weathered rock, while the third layer probably could be fresh basement rock. The thickness of the superficial cover is averagely 2.49m, and the depth to the basement is between 5.2m to 22.9m, the aquifer thickness ranges between 1.67 to 21.1m. The laterite in the second layer shown in some locations is of great importance as it reduces surface run off and aids infiltration into the underlying aquifer. The thickness of the aquifer component in the north-southern half of the study area is large enough to harbour substantial quantity of water. Areas around ZUN 01 and ZUN 05 could be potential areas for groundwater exploration. In this research, the depth to bedrock and aquifer thickness were determined, lithological formations within the overburden were delineated and approximate depths
Keywords: Aquifer, Electrode, Groundwater, Resistivity